2011
DOI: 10.2215/cjn.04160511
|View full text |Cite
|
Sign up to set email alerts
|

Living Kidney Donors Ages 70 and Older

Abstract: SummaryBackground and objectives The profound organ shortage has resulted in longer waiting times and increased mortality for those awaiting kidney transplantation. Consequently, patients are turning to older living donors. It is unclear if an upper age limit for donation should exist, both in terms of recipient and donor outcomes.Design, setting, participants, & measurements In the United States, 219 healthy adults aged Ն70 have donated kidneys at 80 of 279 transplant centers. Competing risks models with matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 26 publications
3
78
1
2
Order By: Relevance
“…Berger et al analysed kidney transplantation results of kidney harvested from a living kidney donors older than 70 years old and they proved there is a correlation between donor's age and transplantation results. However, results are comparable with results of kidney transplantation that were harvested from cadaveric standard criteria donors [2]. In our research there was a correlation between donor's age and kidney function -the older donors were, the higher creatinine serum concentration at recipient.…”
Section: Discussionsupporting
confidence: 84%
“…Berger et al analysed kidney transplantation results of kidney harvested from a living kidney donors older than 70 years old and they proved there is a correlation between donor's age and transplantation results. However, results are comparable with results of kidney transplantation that were harvested from cadaveric standard criteria donors [2]. In our research there was a correlation between donor's age and kidney function -the older donors were, the higher creatinine serum concentration at recipient.…”
Section: Discussionsupporting
confidence: 84%
“…Mortality among living kidney donors aged >70 years was no higher than healthy matched controls drawn from the NHANES-III cohort; in fact, mortality was lower, probably reflecting higher selectivity among older live donors than could be captured in National Health and Nutrition Examination Survey III [5].…”
Section: Discussionmentioning
confidence: 89%
“…In light of the known decrease in glomerular filtration rate with advancing age, several studies have sought to establish the relation between donor age and allograft failure and function following LDKT [9][10][11][12][13]. A recent study by Chang et al [14] showed that, with the exception of recipients aged 18-39 years who had the best outcomes with donors aged 18-39 years, living donor age between 18 and 64 years had minimal effect on the half-life of kidney allografts.…”
Section: Introductionmentioning
confidence: 99%
“…The studies included in this review were mostly small single-center reports and demonstrated significant between-study heterogeneity [15]. More recent studies have focused on the outcomes of kidney transplants from the oldest living donors (i.e., 70 years) [9,10] or had insufficient power to detect nonlinear associations [12,13].…”
Section: Introductionmentioning
confidence: 99%